Effect of Cu addition on the tribological properties and oxidation behavior of nanomultilayered AlTiN/Cu coatings - Haijuan Mei; Rui Wang; Ji Cheng Ding; Junfeng Zhao; Ting Wang; Jianming Deng; Kai Li; Weiping Gong; Qimin Wang (Journal of Materials Research and Technology, 2024)
As a soft metal, the addition of Cu has an important influence on the high-temperature tribological properties and oxidation behavior of nanomultilayered AlTiN/Cu coatings. At room temperature (RT), due to abrasive wear, the AlTiN coating exhibited a high friction coefficient of 0.97 and low wear resistance. After adding Cu layer, the friction coefficient gradually decreased to 0.59 at 18.4 at.% Cu due to the lubricating effect of soft metal Cu and CuO, and the best wear resistance was achieved at 2.9 at.% Cu. At 800 °C, the oxidation resistance sharply reduced after adding Cu layer, and exhibited oxidation delamination. At low Cu contents (≤4.5 at.%), by the inward diffusion of O, a mixed oxide layer of Al2O3, TiO2, and CuO formed. At 18.4 at.% Cu, by the outward diffusion and oxidation of Cu, double-layer oxides formed, and the top layer of CuO contributed to a low friction coefficient of 0.53, but also caused a reduce in the wear resistance.